1987
DOI: 10.1126/science.3798109
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer and Indoor Air Pollution in Xuan Wei, China

Abstract: In Xuan Wei County, Yunnan Province, lung cancer mortality is among China's highest and, especially in females, is more closely associated with indoor burning of "smoky" coal, as opposed to wood or "smokeless" coal, than with tobacco smoking. Indoor air samples were collected during the burning of all three fuels. In contrast to wood and smokeless coal emissions, smoky coal emission has high concentrations of submicron particles containing mutagenic organics, especially in aromatic and polar fractions. These s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
320
3
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(335 citation statements)
references
References 2 publications
9
320
3
3
Order By: Relevance
“…It is unusual to find similar male and female lung cancer mortality rates (27.7 and 25.3 per 100 000, respectively) as in Xuan Wei County (Mumford et al, 1987).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…It is unusual to find similar male and female lung cancer mortality rates (27.7 and 25.3 per 100 000, respectively) as in Xuan Wei County (Mumford et al, 1987).…”
mentioning
confidence: 83%
“…Lung cancer mortality is five times the national average and among the highest in China, yet females despite almost all being nonsmokers have the highest rate in China (eight times the national female average). It is unusual to find similar male and female lung cancer mortality rates (27.7 and 25.3 per 100 000, respectively) as in Xuan Wei County (Mumford et al, 1987).Cigarette smoking has long been established as the predominant risk factor for lung cancer (Doll and Peto, 1978; IARC, 1986). Although an aetiological link between lung cancer mortality and domestic smoky coal use (polycyclic aromatic hydrocarbons) has been shown, the causes of lung cancer in Xuan Wei County have remained unexplained (Mumford et al, 1987;He et al, 1991).…”
mentioning
confidence: 99%
“…Previous studies have revealed that high exposure to these genotoxic compounds is associated with several types of cancers, such as lung cancer and pancreatic cancer (Chuang et al, 1992;Anderson et al, 2002). Mumford et al (1987) found that the high lung cancer mortality rates in Xuan Wei, China were related to the residents' lifetime exposure to heavy smoke from the domestic use of charcoal. Chuang et al (1992) further showed that the concentration levels of PAHs in smoky charcoal samples were about one to two orders of magnitude higher than those of the smokeless charcoal samples, and the PAH fractions have high mutagenic activity.…”
Section: Introductionmentioning
confidence: 97%
“…In fact, the death rate was 8 times higher than the national average and 17 times higher than the rest of the province 3 . But change was taking root.…”
Section: Fanning the Flamesmentioning
confidence: 84%
“…Mumford and her colleagues explained that although women in Xuanwei rarely smoked tobacco, at home they cooked food over open fire pits that burned smoky coal 3 . Families also used coal to heat their houses and closed the shutters on their windows to keep the cold out, which trapped smoke and particulate matter inside.…”
Section: Fanning the Flamesmentioning
confidence: 99%